Cicero among the Martyrs: A Reassessment of the First Edition of Nicholas Grimald’s Thre bokes of duties (1556) - Schmidt, Gabriela (Renaissance and Reformation / Renaissance et Réforme, 2020)
Nicholas Grimald’s translation of Cicero’s De officiis has long been revered as the standard version of one of the most popular Tudor school texts, as well as one of the first contributions towards a theory of translation in English. This article reassesses the work’s cultural and political impact through a close examination of its paratexts within the immediate publishing context at the office of Richard Tottel in 1556. It argues that Tottel’s material presentation of the book in a larger publishing program subtly re-encodes the work’s political, ideological, and religious message for his Marian readership. Tottel’s strategy in publishing Grimald’s Duties at this juncture was both to reclaim Cicero’s authority for the Marian program of Catholic restoration and to invest this program with the humanist credentials of influential early Tudor educational reformers.